A Survey of Health, Safety and Environment (HSE) Management and Safety Climate in Construction Sites - Mobaraki, A.; Mirzaei, R.; Ansari, H. (Engineering, Technology & Applied Science Research, 2017)
The principles of health, safety and environment (HSE) in different development activities, including construction, are constantly gaining in significance. This study aims to evaluate the condition of HSE management and safety climate in construction sites. In this descriptive-analytic study, 111 male employees are randomly selected. To determine HSE condition and management and safety climate condition, the NOSACQ questionnaire was used. The collected data are analyzed using SPSS. Based on data analysis a significant relationship between the mean scores of safety climate, job groups and HSE management system with job groups, education and experience (P<0.05) was found. The study results show that HSE management and safety climate in sites are relatively acceptable, that the perception of safety had no special association with age, work experience, education and that the creation of a safety climate depends on the people high in the hierarchy.